2022
DOI: 10.1017/cjn.2022.344
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Stroke Best Practice Recommendations: Acute Stroke Management, 7th Edition Practice Guidelines Update, 2022

Abstract: The 2022 update of the Canadian Stroke Best Practice Recommendations (CSBPR) for Acute Stroke Management, 7 th Edition, is a comprehensive summary of current evidence-based recommendations, appropriate for use by an interdisciplinary team of healthcare providers and system planners caring for persons with an acute stroke or transient ischemic attack. These recommendations are a timely opportunity to reassess current processes to ensure efficient access to acute stroke diagnostics, treatments and management str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 85 publications
0
31
0
Order By: Relevance
“…[20][21][22] The AcT trial was the first phase 3 RCT to compare intravenous tenecteplase with alteplase in all patients presenting with acute ischemic stroke within 4.5 hours from symptom onset and eligible for thrombolysis with alteplase. 23 The trial showed that tenecteplase (0.25 mg/kg) was noninferior to alteplase (0.9 mg/kg) in treatment of acute ischemic stroke (unadjusted risk difference, 2.1% [95% CI, −2.6 to 6.9]) and comparable for all other secondary and safety outcomes. 7 These results have changed Canadian, European, and Australian guidelines, all of which now recommend the use of tenecteplase for acute ischemic stroke within 4.5 hours of symptoms onset.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[20][21][22] The AcT trial was the first phase 3 RCT to compare intravenous tenecteplase with alteplase in all patients presenting with acute ischemic stroke within 4.5 hours from symptom onset and eligible for thrombolysis with alteplase. 23 The trial showed that tenecteplase (0.25 mg/kg) was noninferior to alteplase (0.9 mg/kg) in treatment of acute ischemic stroke (unadjusted risk difference, 2.1% [95% CI, −2.6 to 6.9]) and comparable for all other secondary and safety outcomes. 7 These results have changed Canadian, European, and Australian guidelines, all of which now recommend the use of tenecteplase for acute ischemic stroke within 4.5 hours of symptoms onset.…”
Section: Discussionmentioning
confidence: 98%
“…7 These results have changed Canadian, European, and Australian guidelines, all of which now recommend the use of tenecteplase for acute ischemic stroke within 4.5 hours of symptoms onset. [23][24][25] Unlike the clinical practice guidelines, regulatory approval for intravenous alteplase use in patients with acute ischemic stroke is restricted to patients presenting within 3 hours of stroke symptom onset. 10,11 This key secondary analyses from the AcT trial aims to therefore present in detail the effect of tenecteplase versus alteplase in the early versus late (3-4.5 hours) presenters while also assessing if the well-known relationship of time to thrombolysis on outcomes with alteplase is also seen with tenecteplase.…”
Section: Discussionmentioning
confidence: 99%
“…All patients in the sham and intervention arm will receive standard of care management for ischemic stroke as per the Canadian Stroke Best Practices Guidelines [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…For the late window (6-24 hours) however, both the American Heart Association and Canadian Stroke Best Practices recommend that perfusion CT neuroimaging (NCCT, CTA and perfusion imaging) be utilized to allow for more nuanced patient selection. 6,7 These recommendations are driven by use of perfusion imaging in late-window EVT trials. Both DAWN and DEFUSE 3, used perfusion imaging to derive quantitative values for core infarct and excluded those that were considered to have a large core.…”
Section: Introductionmentioning
confidence: 99%